Avoiding Cyberspace Catastrophes through Smarter Testing. - Vassilev, Apostol; Celi, Christopher (Computer (00189162), 2014)
The Heartbleed bug highlighted a critical problem in the software industry: inadequately tested software results in serious security vulnerabilities. Available testing technologies, combined with emerging standards, can help tech companies meet increasing consumer demand for greater Internet security.